Four Sub-Channel Single Sideband Generation of Vector mm-Wave Based on an I/Q Modulator - Wen Zhou; Li Zhao; Jiao Zhang; Kaihui Wang (IEEE Photonics Journal)
In this paper, a novel scheme to generate multichannel single sideband (SSB) optical signals enabled by one single I/Q modulator based on digital signal processing (DSP) is proposed, which is more flexibility and stability for the future 5G broadband access network instead of complex multiple lasers construction. Four sub-channels carrying different vector quadrature amplitude modulated (QAM) data are modulated to the upper sideband (USB) by I/Q modulation, while the vector unmodulated RF signal is located at the lower sideband (SSB) of the suppressed center carrier. They are used to generate four different mm-wave carriers after heterodyne beating. Due to the imbalance effect of I and Q components from the I/Q modulator, we also optimize the frequency of USB and LSB to reduce the crosstalk between the USB and LSB signal. The experimental results indicate that four-channel QPSK (2 × 2 × 4 = 16 Gbit/s) and 16-QAM (2 × 4 × 4 = 32 Gbit/s) signals with 5 GHz channel spacing at Q-band can be transmitted over 80 km single-mode-fiber 28 and 0.5 m wireless link without dispersion compensation.